Incident Instrumental Activities of Daily Living Difficulty in Older Adults: Which Comes First? Findings From the Advanced Cognitive Training for Independent and Vital Elderly Study - Feger, Danielle M.; Willis, Sherry L.; Thomas, Kelsey R.; Marsiske, Michael; Rebok, George W.; Felix, Cynthia; Gross, Alden L. (Frontiers in Neurology, 2020)
Introduction: Instrumental activities of daily living (IADLs) are complex daily tasks important for independent living. Many older adults experience difficulty with IADLs as their physical and/or cognitive function begins to decline. However, it is unknown in what order IADLs become difficult. Methods: Participants from the Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE) study who were free of IADL difficulty at baseline (N=1,277) were followed up to 10 years until first reported IADL difficulty. A total of 19 IADL tasks were grouped into 7 task categories. A discrete-time multiple-event process survival mixture model (MEPSUM) was used to generate hazard estimates of incident IADL difficulty in 7 groups from ages 65-80. Hazard estimates were compared in the three intervention groups (memory, inductive reasoning, speed of information processing) versus the no-contact control group. Results: A total of 887 (69.5%) participants reported incident difficulty in at least one IADL task category. Compared to individuals who remained free of IADL difficulty, those who reported incident difficulty were more likely to be older, female, and have lower Short Form 36 general health scores. The IADL task categories to first become difficult were housework, managing health care, and phone use. There were no differences by intervention group in the hazard estimates of incident IADL difficulty. Conclusion: Managing health care and phone use are more cognitively-demanding IADLs, and individuals who experience difficulty in these tasks first may be more likely to experience cognitive decline. Recognizing early difficulty in managing health care may allow for implementation of compensation strategies to minimize unintentional medication misuse, increased adverse medical events, and unnecessary hospitalization. Training of a specific cognitive domain may not influence ordering of IADL difficulty because IADL tasks require proficiency in and integration of multiple cognitive domains.